Storied Revelations Parables, Imagination and George MacDonald's Christian Fiction. - Kreglinger, Gisela H. (Havertown : The Lutterworth Press, 2014)
George MacDonald, the Victorian poet and theologian, observed that his was a culture saturated with Christian jargon but often void of a profound understanding of the gospel for its own time and culture. The language of Scripture no longer penetrated people's hearts, thoughts, and attitudes; it no longer transformed people's lives. MacDonald, called to be a pastor, turned to story and more specifically the ""parabolic"" as a means of spiritual awakening. He created fictive worlds in which the language of Jesus would find a new home and regain its revelatory power for his particular Victorian a.
Front cover; Title page; Copyright; Contents; Foreword by Eugene H. Peterson; Acknowledgments; Introduction; 1. George MacDonald: Poet and Theologian; 2. Patterns of Subversion and Promise: Jesus'' Parables; 3. Patterns of Subversion and Promise: Romanticism; 4. George MacDonald''s Theological Rationale for Story and the ""Parabolic""; 5. Patterns of Subversion and Promise: Lilith; Conclusion; Bibliography; Back cover.
Print version record.
Master record variable field(s) change: 072
Keywords: MacDonald, George, -- 1824-1905 -- Criticism and interpretation; Jesus Christ -- Parables; Jesus Christ; MacDonald, George, -- 1824-1905.; Imagination; Parables; Christian fiction -- History and criticism; Bible and literature; RELIGION -- Christian Theology -- Systematic; RELIGION -- Christianity -- General; Bible and literature; Christian fiction; Imagination; Parables; Parables, Biblical; RELIGION / Biblical Studies / Exegesis & Hermeneutics; Electronic books; Criticism, interpretation, etc